EFFECTIVE WAYS OF TEACHING PREPOSITIONS - Malika Toʻraqulova Sidiq qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation. This article explores various strategies and techniques for effectively teaching prepositions in language education. Prepositions are essential elements of language that often pose challenges to learners, both native and non-native speakers. In this article, we discuss the importance of teaching prepositions and provide a comprehensive analysis of literature related to preposition instruction. We then present a range of methods for teaching prepositions, along with the results of studies that have investigated their efficacy. The discussion section highlights the strengths and limitations of these methods, and we conclude with suggestions for improving preposition instruction in the classroom.